Collecting duct–specific knockout of endothelin-1 causes hypertension and sodium retention - Ahn, Dowhan (American Society for Clinical Investigation, 2004)
In vitro studies suggest that collecting duct–derived (CD-derived) endothelin-1 (ET-1) can regulate renal Na reabsorption; however, the physiologic role of CD-derived ET-1 is unknown. Consequently, the physiologic effect of selective disruption of the ET-1 gene in the CD of mice was determined. Mice heterozygous for aquaporin2 promoter Cre recombinase and homozygous for loxP-flanked exon 2 of the ET-1 gene (called CD-specific KO of ET-1 [CD ET-1 KO] mice) were generated. These animals had no CD ET-1 mRNA and had reduced urinary ET-1 excretion. CD ET-1 KO mice on a normal Na diet were hypertensive, while body weight, Na excretion, urinary aldosterone excretion, and plasma renin activity were unchanged. CD ET-1 KO mice on a high-Na diet had worsened hypertension, reduced urinary Na excretion, and excessive weight gain, but showed no differences between aldosterone excretion and plasma renin activity. Amiloride or furosemide reduced BP in CD ET-1 KO mice on a normal or high-Na diet and prevented excessive Na retention in salt-loaded CD ET-1 KO mice. These studies indicate that CD-derived ET-1 is an important physiologic regulator of renal Na excretion and systemic BP.